Lysine Catabolism Through the Saccharopine Pathway: Enzymes and Intermediates Involved in Plant Responses to Abiotic and Biotic Stress - Arruda, Paulo; Barreto, Pedro (Frontiers in Plant Science, 2020)
The saccharopine pathway (SACPATH) involves the conversion of lysine into -aminoadipate by three enzymatic reactions catalyzed by the bifunctional enzyme lysine-ketoglutarate reductase/saccharopine dehydrogenase (LKR/SDH) and the enzyme -aminoadipate semialdehyde dehydrogenase (AASADH). The LKR domain condenses lysine and -ketoglutarate into saccharopine, and the SDH domain hydrolyzes saccharopine to form glutamate and -aminoadipate semialdehyde, the latter of which is oxidized to -aminoadipate by AASADH. Glutamate can give rise to proline by the action of the enzymes Δ1-piperideine-5-carboxylate synthetase (P5CS) and Δ1-piperideine-5-carboxylate reductase (P5CR), while Δ1-piperideine-6-carboxylate the cyclic form of -aminoadipate semialdehyde can be used by P5CR to produce pipecolate. The production of proline and pipecolate by the SACPATH can help plants face the damage caused by osmotic, drought, and salt stress. AASADH is a versatile enzyme that converts an array of aldehydes into carboxylates, and thus, its induction within the SACPATH would help alleviate the toxic effects of these compounds produced under stressful conditions. Pipecolate is the priming agent of N-hydroxypipecolate (NHP), the effector of systemic acquired resistance (SAR). In this review, lysine catabolism through the SACPATH is discussed in the context of abiotic stress and its potential role in the induction of the biotic stress response.